Long-Term Outcomes After Transfemoral-Transcatheter Aortic Valve Implantation in Very Old Patients Using the Balloon-Expandable Bioprosthesis. (5th January 2022) - Useini, Dritan; Schlömicher, Markus; Aweimer, Assem; Haldenwang, Peter; Strauch, Justus; Patsalis, Polykarpos C.
Transcatheter aortic valve implantation (TAVI) can be safely performed in old patients. Increasing longevity raises often the question whether TAVI can be still useful for patients beyond a certain age limit. Data on long-term outcomes of elderly patients after TAVI are sparse. We sought to assess the impact of very advanced age on long-term outcomes after transfemoral (TF)-TAVI. Data of 103 patients undergoing TF-TAVI with the balloon-expandable bioprosthesis between May/2014 and May/2019 were analyzed. We divided the cohort into two age groups: ≥85 years (group1: n = 37; 87.5 ± 2.6 years; STS-Score 3.9 ± 1.4) versus < 85 years (group2: n = 66; 80 ± 3.1 years; STS-Score 3.4 ± 1.8). We conducted up to 6 years clinical follow-up. Overall mortality at 30 days was 3.8% without significant differences between the two age groups. Incidence of major vascular injury (8.6 vs. 6.3%, p = .695) and stroke (2.8 vs. 3%, p = 1) was not significantly different between group 1 and 2, respectively. More than mild paravalvular leakage was found in 1 patient (group 1). The mean long-term survival probability was 51.3 months [95% CI: 42.234–60.430] in group 1 versus 49.5 months [95% CI: 42.155–56.972] in group2 ( p = .921). Long-term outcomes of very old patients after TF-TAVI show a similar treatment benefit compared to the younger patients.